Relationship of moderate to heavy Trichuris trichiura infection with the packed red cell volume and mental ability of elementary schoolchildren in Miag-ao, Iloilo - Calibjo, Hartzell M.; Calvo, May Lyn A. (2005.)
Trichuris trichiura commonly known as whipworm is a nematode that infects human particularly school-aged children. Studies shows that moderate to heavy Trichuris infection may adversely affect the cognitive functions of schoolchildren (Nokes, 1991) and may cause anemia ovetime (Politt, 1982). However this has not been established in the local setting. This led the researchers to locally conduct a study that would primarily determine the relationship of the moderate to heavy intensity of Trichuriasis with the mental ability of schoolchildren and with the Packed Red cell volume.
Special Problem (Undergraduate, Bachelor of Science in Public Health)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Trichuris trichiura